Discernment in Origen of Alexandria - P. B. Decock (Acta Theologica)
Origen was the first Christian writer to reflect more systematically on the theme of discernment; his views have greatly influenced later spiritual writers. This article aims at situating Origen’s understanding of discernment within his view of creation, of anthropology and of spiritual growth. Discernment is viewed as an operation of the higher part of the soul (nou/j), whereby the soul opens itself to its spirit. As such it is able to accept divine guidance from the Holy Spirit and the Logos in order to assess the movements of the soul and to manage these correctly so that the soul may preserve what is good and continue to strive for better things. As the “intelligence” is created after the image of God, the Logos, its fulfilment lies in a cooperative movement with the Logos towards ever greater likeness with God. Progress in virtue, knowledge and happiness are an ever more intense participation in the Logos who himself is every virtue, all wisdom and love. As a result of this participation, the “intelligence” becomes ever more “like” the Logos and, therefore, becomes ever more capable of understanding and discerning.